Dopaminergic genetic variation and response to social comparative feedback when learning a motor sequence task - Allison F. Lewis; Rachel Bohnenkamp; Jill Campbell Stewart (PLoS ONE, 2026)
Positive social comparative feedback during motor skill practice is hypothesized to enhance motor learning by triggering a dopaminergic response. Individual differences in dopamine-related genes impact dopamine neurotransmission and may influence responsiveness to motor practice conditions that target dopaminergic pathways. The purpose of this study was to examine the impact of dopamine genotype on learning of a motor sequence task under two different feedback conditions: response time only feedback or response time with positive social comparison. Fifty-two adults practiced a joystick-based motor sequence task over two consecutive days. On Day 1, participants were randomized to receive either 1) response time only feedback (i.e., “You completed the block in 80 seconds”) or 2) positive social comparative feedback (i.e., “You completed the block in 80 seconds. You were faster than others”). Motor learning was assessed by retention performance, or the change in response time from the first block of Day 1 to the first block on Day 2. Saliva samples were used to genotype for dopamine receptors DRD1, DRD2 and DRD3 and COMT. Individual genes were scored (0–2) and summed to create a polygene score (0–8). Participants were then categorized as having Low (1–4) or High (5–8) dopamine neurotransmission. A significant interaction was found between time, summary polygene group and feedback group (p = 0.048). The Low dopamine group showed greater improvements with response time only feedback versus positive social comparative feedback. The High dopamine group showed similar improvements in response time regardless of feedback type. This suggests that feedback targeting dopaminergic pathways may not be beneficial for individuals with lower dopamine neurotransmission. Our findings suggest that dopaminergic genetics may impact the efficacy of positive social comparative feedback on motor learning in low dopamine genotypes.